Nanophosphors-Based White Light Sources - Maura Cesaria; Baldassare Di Bartolo (Nanomaterials, 2019)
Miniaturization requests and progress in nanofabrication are prompting worldwide interest in nanophosphors as white-emission mercury-free lighting sources. By comparison with their bulk counterparts, nanophosphors exhibit reduced concentration quenching effects and a great potential to enhance luminescence efficiency and tunability. In this paper, the physics of the nanophoshors is overviewed with a focus on the impact of spatial confinement and surface-to-volume ratio on the luminescence issue, as well as rare earth-activated multicolor emission for white light (WL) output. In this respect, the prominently practiced strategies to achieve WL emission are single nanophosphors directly yielding WL by means of co-doping and superposition of the individual red, green, and blue emissions from different nanophosphors. Recently, a new class of efficient broadband WL emitting nanophosphors has been proposed, i.e., nominally un-doped rare earth free oxide (yttrium oxide, Y2O3) nanopowders and Cr transition metal-doped garnet nanocrystals. In regard to this unconventional WL emission, the main points are: it is strictly a nanoscale phenomenon, the presence of an emitting center may favor WL emission without being necessary for observing it, and, its inherent origin is still unknown. A comparison between such an unconventional WL emission and the existing literature is presented to point out its novelty and superior lighting performances.